Charles Knowles Bolton journal - Bolton, Charles Knowles, 1867-1950.
Journal (17 pages).
Antiquarian, librarian, and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Antiquarians; Educators; Librarians